Behaviour of Holstein Friesian cows with different milk production ability during milking - Szenléleki, Andrea; Zengő, György; Széplaki, Kálmán; Kékesi, Károly; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
Authors’ aim was to determine the difference in temperament between cow groups with different milk production ability at milking. Examinations were carried out on Péteri farm (Budapest), with 21 primiparous (average age in May: 2.7 ± 0.18 years) and 19 multiparous (average age in May: 4.5 ± 0.70 years) Holstein Friesian cows, at the middle of the lactation, from May to August. Temperament was assessed once each month, during morning milking in a herringbone-type milking parlour, in a 5-point scale during udder preparation process and milking procedure (1: very nervous, continual and vigorous stepping and kicking, 5: very quiet, no leg movements). Among milk production traits milk yield and milk flow were collected individually on each test day morning. Data were processed with SPSS. 14.0 statistical program package (Cluster-analysis, Kruskal-Wallis test). Three groups were formed by Cluster-analysis (1st group, n = 19, 2nd group, n = 10, 3rd group, n = 11) from the cows investigated in the first month (May), by milk yield and milking speed. The cow groups significantly differed in both milk production traits (P < 0.001). There were not any differences between groups either in temperament before or temperament during milking in each month (before milking: May, June, July, August, P > 0.10; during milking: May, June, July, August, P > 0.10). This result implies that individuals in three groups had very similar behavioural patterns both of before and during milking. Temperament is needed to observe permanently in aspects of manageability and animal welfare in Hungary, as well.
Keywords: temperament; lactation; milk production; milking speed; Holstein Friesian breed